PENGARUH KUALITAS STRATEGI PEMASARAN TEHADAP EVEKTIVITAS SALURAN DISTRIBUSI MELALUI SELLING-OUT DAN SELLING-IN KINERJA PEMASARAN - R. Kurniawan Dwiseptiady (E-Jurnal Kajen, 2017)
Some companies want high profit and sustainable for their life, for thisthe purpose they must compete with each other to have the best performance.Developing the greatest market performance needs an excellent strategy andmaximum effort in all departments. Market performance can be achievedfrom a good selling by selling-out or selling-in activities. To create a goodselling cannot be reached without effective distribution channels and qualityof the marketing strategy. This research tests how to enhance marketperformance by those variables. Data gained from 105 wholesaler garmentmanagers or owners in Pekalongan Central Java in this research isacceptable, it is shown by chi-square 192,362, GFI, 0,858, AGFI, 0,21, CMIN/DF, 1,045, TLI, 0,993, CFI, 0,994, those number indexes are standardalthough AGFI and GFI index accepted marginally. Findings show thatmarket performance can be achieved from selling-out and selling-in withthe effectiveness of distribution channels and the quality of marketing strategyconcludes with a discussion of managerial implications and for futureresearch.